America(n)-Nature, conquestual habitus and the origins of the “Anthropocene”. Mine, Plantation and their geological (and anthropological) impacts - Machado Aráoz, Horacio (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Since its irruption, the “Anthropocene” voice has provoked a profound epistemic and political upheaval, revealing the critical radicality of the threats to life on Earth. By placing as a horizon of intellection the devastating balance that the predominant course of human events has printed on the Planet, said concept designates more than a discussion on the nature of the present geological age. It has opened a new dimension in the understanding of the interlinkages between the ecological and the political; a new problematization on the nature of the affections between the anthropological and the geological. On this plane, from our previous research, this article aims to highlight the excluding centrality of America(n)-Nature as the historical-geographical origin and constituent epistemic-political principle of this new Era. After a review of the critical reception that the concept has given rise to in the field of the Social Sciences, the paper invites us to review the “Anthropocene” on the basis of an elementary shift of gaze: from “nature” to history; from the species to social formations; from substances (carbon, uranium, plastics) to practices, ways of life and power relations. By investigating its genealogy from the decolonial critical materialism of the Political Ecology of the South, the environment of the “conquest of America” is explored as a geological-political turning point that gave rise to the emergence of a new geo-sociometabolic regime. This approach visualises the Conquestnot only in terms of its immediate catastrophic impact (Pico Orbis), but also as a geo-historical ground where a new matrix of relationships (conquestual habitus) between humans and non-humans, between the biological and the political, was forged, which would end up disrupting the dynamics of flows and sociometabolic cycles of terrestrial life. It aims to highlight the ontological effects (geological, anthropological and socio-political) of those original practices of extractivist occupation/appropriation of territories and populations. It is postulated that these practices - configured and sedimented through the establishment, expansion and generalization of the Mine and Plantation forms as technologies of power and new means of conception and production of human and terrestrial existence in general – would have most probably been the triggers of the geosocial emergence in which the human species has now become gravely involved.